Residential buildings with brain-computer interface functionality: An elevator case study. (March 2022) - Chatziparasidis, Iraklis; Sfampa, Ioanna K
Brain–computer interfaces (BCI) are systems that use signals recorded from the brain to enable communication and control applications. One of the most important applications of BCI technology is that enables people who are severely paralyzed by amyotrophic lateral sclerosis, brainstem stroke, or other disorders to communicate, operate computer programs, or even control numerous devices. Moreover, elevators are probably the best option for disabled persons to expand their access and mobility within a house or a building. In this study, a prototype application is presented, together with an experimental setup of a BCI system that attempts to control an elevator. Practical application: Many researchers are dealing with BCI systems that give the possibility to disabled people to control a variety of devices from wheelchairs to different home appliances, using the signals of their brain and forming a smart home services framework. This work comes to support this effort by presenting a case study, as a proof of concept, for an elevator BCI system that could be part of a complete "smart" home BCI system. The presented experimental setup proves that elevators with BCI functionalities are practically feasible and in an affordable cost, and that they could be a significant element within a "smart" residential building.